Key concepts in medieval literature - Solopova, Elizabeth (Palgrave key concepts Literature, 2007)
"Key Concepts in Medieval Literature provides the reader with an introduction to the major authors, themes and critical perspectives in Old and Middle English literature. Together with looking at significant authors and works in the period, the book emphasises the key historical and literary concepts that inform the evolution of literature through the age. Short contextual essays offering an overview of relevant historical and philosophical themes accompany the literary discussion. Clearly presented, the book merges essential analytical and technical skills with contemporary literary discussions, allowing the reader to become aware of the breadth and depth of such a large and diverse genre."--Jacket.